Financial Comparison Analysis of Micro, Small and Medium Enterprises Processed Fisheries During the Pandemic and New Normal in Makassar City - Sani, A. Nadia Mughsita; Baso, Aris; Cangara, Arie Syahruni; Made, Sutinah; Tahang, Hamzah (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2023)
This study aims to determine the income received, business feasibility and Marketing System for Micro, Small and Medium Enterprises Processed Fisheries during the Pandemic and New Normal in the city of Makassar. This research was carried out in December 2021. The sampling method used was the Purposive Sampling method with the following criteria, those who were actively producing during the pandemic and New Normal had employees, who processed and marketed processed fishery products, had a place of business and business support infrastructure. and willing to be interviewed. The data sources used are primary data and secondary data and then analyzed using cost and income analysis as well as business financial analysis. Fishery Processed Micro, Small and Medium Enterprises in Makassar City experienced changes or increases starting from the total costs used, revenues and profits obtained during the COVID-19 pandemic to the New normal period. The impact of the COVID-19 pandemic on fishery-processed Micro, Small and Medium Enterprises in Makassar City is 13% of Micro, Small and Medium Enterprises that are not producing during the COVID-19 pandemic, which means the business is experiencing losses or not getting a profit and only 87% of Micro, Small and Medium Enterprises are producing during the COVID-19 pandemic, which means the business is profitable. New normal, all Micro, Small and Medium Enterprises are starting to return to production so that their businesses again have profits and the production process is in accordance with the processing in their business. The feasibility level of Micro, Small and Medium Enterprises processing fisheries during the COVID-19 pandemic and the New normal COVID-19 in Makassar City shows the criteria R/C > 1, which means that the business being run is profitable or the Micro, Small and Medium Enterprises processed fisheries in Makassar City are feasible.